MANTRA PENGASIH DIRIK PENINGGALAN DARI MASA LALU - Agustina, Mita; Effendy, Chairil; Martono, Martono (Universitas Tanjungpura, 2023)
This study aims to determine the structure and implementation of the love spell left over from the past. The research method used is descriptive with a qualitative form. The approach used is a structural approach. The data source for this research is the result of interviews and the research data is in the form of a compassionate mantra text. Data collection techniques used in this study were interview techniques and recording techniques. The data validity testing technique is to use observation persistence and reference adequacy. The results of the research regarding the text of the mantra relics of relics from the past, there are imagery or imagery, namely visual imagery, touch imagery, tasting imagery, auditory imagery, and feeling imagery. Concrete words are found in almost all the lines of compassionate mantras that are dominant with visual images. The rhymes contained in the self-love mantra include rhymes based on sound, there are full rhymes, absolute rhymes, half rhymes, alliteration rhymes, associative rhymes, and dissonant rhymes. Based on the location of the rhymes in the line, there are initial rhymes, middle rhymes and ending rhymes. Rhymes based on the location of the pair in the line, there are twin rhymes, broken rhymes, cross rhymes, continuous rhymes, and free rhymes. The implementation of learning in this study was realized by the preparation of lesson plans for the 2013 curriculum for class VII junior high schools.